Case Report:Pemberian Terapi Relaksasi Genggam Jari terhadap Tingkat Nyeri pada Pasien Nyeri Akut Post Apendektomi - Ratih Widya Retnaningrum; Dyah Rivani; Suprianto Suprianto (Pusat Riset dan Inovasi Nasional, 2024)
After appendectomy, patients tend to experience pain due to the surgical wound. The non-pharmacological technique of finger-hold relaxation therapy is one of the pain management methods for patients. This case study aims to determine the effectiveness of finger grip relaxation on pain levels in patients with acute pain after appendectomy. This research is a case report with the intervention of stopping finger hold relaxation therapy which was carried out for 3 days. The results of this case study show that after the finger-hold relaxation therapy intervention was carried out for 3 days, there was a decrease in the level of pain from scale 7 to scale 2. Finger-hold relaxation was effective in reducing pain in post-appendectomy patients.